The Role of Critical Life Events in the Development of Authentic Leadership and its Socioeconomic Outcomes: An Empirical Study - Njine, Brian King Mbugua; Ndonye, Davies (Human Resource and Leadership Journal, 2026)
Purpose: The study explored the moderating effect of critical life events on the relationship between developmental life attributes, authentic leadership, and its subsequent socioeconomic outcomes. Methodology: Anchored on Moral Development Theory, Psychodynamic Theory, and Life Course Theory, the study adopted a convergent parallel research design. Both quantitative and qualitative data was drawn from a combined sample of 417 media professionals in Nairobi County, Kenya, using a questionnaire and an interview guide respectively. Findings: Findings demonstrated that childhood adversities as well as formative experiences significantly amplify the contribution of psychological attributes (β = .137, p<0.05) and sociological attributes (β=0.188, p<0.05) in the formation of authentic leadership, improving explanatory power by 29.2% and 9.6% respectively. Results further revealed that adulthood events, such as career transitions, loss of income, family responsibilities, and health challenges significantly moderate the influence of authentic leadership on socioeconomic outcomes (β=0.220, p<0.05), enhancing model’s explanatory power by 13%. Respondents affirmed that when authentic leadership is strengthened through adaptive responses to critical life events, it is positively associated with socioeconomic outcomes including career progression, organizational citizenship, and greater positive social influence. Unique Contribution to Theory, Policy and Practice: The study recommends the integration of life-phase experiences into leadership development frameworks, emphasizing how personal growth trajectories contribute to broader socioeconomic success. Policy makers can adopt a holistic approach by providing resources to employees undergoing CLE, thereby creating environments where adversity fuels growth and positive socioeconomic outcomes.